Manzoni politico - DI BENEDETTO, Arnaldo (Giornale storico della letteratura italiana, 2011)
Abstract The author traces the political itinerary of Alessandro Manzoni through his most clearly ‘engaged’ writings: from his early short poem Il trionfo della Libertà , in which strong criticism is expressed even of the new government imposed by Napoleon from Milan, to the unfinished historical essay Dell’indipendenza italiana. The recurring theme running through these writings is Italian independence - or at least in some cases, that of Lombardy. Manzoni shared the new nationalist ideology that established itself in Europe with the advent of the French Revolution. He reached a centralist and anti federalist conception of the desired new Italian State. He dedicated particular attention to the spread of a single language, common to all Italians.